Osteopontin And Angiogenic Factors As New Biomarkers Of Prostate Cancer - Wisniewski, Tomasz; Zyromska, Agnieszka; Makarewicz, Roman; Zekanowska, Ewa (Urology Journal, 2019)
Purpose: The novel biomarkers that would identify patients at risk for relapse and metastatic spread are needed. The aim of this study was the evaluation of serum levels of osteopontin (OPN) and tumor endogenous angiogenic factors such as vascular–endothelial growth factor (VEGF), vascular-endothelial growth factor receptor 2 (VEGF R2), endostatin, angiostatin and thrombospondin 1, in prostate cancer (PC) patients. Material and Methods: Blood concentrations of the analyzed parameters were determined in 40 prostate cancer patients eligible for radiotherapy as well as in the control group consisted of 25 volunteers. Commercial ELISA kits were used for the analysis. Results: Significantly higher levels of OPN (101.49 ng/mL vs 59.88 ng/mL; P<.001), endostatin (252.60 ng/mL vs. 223.55 ng/mL; P=.043), angiostatin (47 ng/mL vs. 13 ng/mL; P=.047), VEGF (262.1 pg/mL vs. 138.0 pg/mL; P=.056) and VEGF R2 (11188.81 pg/mL vs. 9377.50 pg/mL; P=.047) were detected in PC patients compared with the control group. In PC patients we showed a positive correlation between OPN level and TNM clinical stage(R=0.36; P=.02) and negative correlation between OPN level and hemoglobin concentration (R=-0.33; P=.04). Conclusion: The study showed higher levels of the angiogenic factors in PC patients compared with the control group and identified OPN as an indicator of the PC clinical stage as well as a decreased hemoglobin level.